The performance of Islamic banking among the commercial banks in Malaysia / Samsuwatd Zuha Mohd Abbas, Norli Ali and Aminah Mohd Abbas - Mohd Abbas, Samsuwatd Zuha; Ali, Norli; Mohd Abbas, Aminah (Research Management Institute (RMI), 2008)
This paper examines the accounting performance of the Islamic banking among (??) commercial banks in Malaysia. A total of 18 commercial banks which include 4 Islamic banks are selected as samples covering the period of 2000 - 2006. Accounting performance is measured by the return on assets (ROA) and return on equity (ROE). The objective of the study is (1) to determine whether Islamic banking performance is at par with the conventional banking and (2) to investigate whether the type (Islamic or conventional bank) and age of bank influence the performance. Result of the independence t-test of the study shows that there is no significant difference in the performance of the Islamic and the conventional banking in Malaysia although the mean score for conventional banking is higher. The regression results show that the age of banks has a positive impact on the bank performance where as none of the types of banks influence performance.